Factors Influencing Adoption of Scientific Technologies Related to Makhana (Euryale ferox)-Cum-Fish Culture in Bihar (Indian Journal of Extension Education, 2018)
In India makhana is being cultivated particularly in North Bihar and lower Assam. In spite of availability of profitable and farmers’ friendly technology in relation to makhana-cum-fish culture, its cultivation is confined in small pocket of India due to various reasons. The present study made an attempt to study the factors responsible for the adoption of scientific makhana-cum-fish culture technologies. The results of the study showed that 85 percent of farmers adopted makhana-fish farming practices. Correlation analysis of the data revealed that education, type of house and annual income are positively and significantly correlated with production level, whereas physical feature and contour type were negatively correlated with production level. It is found that annual income and type of house are correlated with adoption of makhana cum fish culture practices.